Design and realization of a 3-K cryostat for a 10-cm ultrastable silicon cavity - Wang, Wen-Wei; Chen, Zhi-Ang; Zhang, Han; Du, Shize; Wu, Rui; Qiao, Chang; Kuang, Shiyin; Zhang, Xibo (Frontiers in Physics, 2023)
Crystalline optical cavities operating at cryogenic temperatures provide a promising route for realizing the next generation of ultrastable lasers with extremely low thermal noise floor. However, it remains challenging to realize a closed-cycle cryostat for cooling a relatively long cavity to very low temperatures. Here we report on the design and experimental realization of a cryostat operating continuously at 3.1 K for an ultrastable 10-cm silicon cavity. Based on a combination of active temperature control and passive thermal damping, we realize at 3.1 K a two-second temperature instability of 6× 10^-8 K for the cavity. By implementing separate supporting structures for the cryocooler and the sample chamber, we realize vibration control on the 1× 10^-7g level at one second in each spatial direction, where g is the gravitational acceleration. With all these features, our cryostat can support an ultrastable silicon cavity with instability near its fundamental thermal noise floor at averaging time of 1 to 50 s. With proper upgrading, our platform holds promise for realizing ultrastable lasers with 3× 10^-17 or better frequency stability, which will in turn enable numerous studies on precision metrology and quantum manybody physics.